Organization of engineering works during demolition of a road section - Kovačević, Nenad V. (Vojnotehnički glasnik / Military Technical Courier, 2015)
When using explosive ordnance for the demolition of elements, materials and facilities, organization is very important in the preparation of works as well as during demolition itself. In the Army of Serbia, for this kind of works, there are specialized expert units within Land Forces engineering battalions or brigades. The organization of the engineering work given in the article is a purposeful solution, regarding the use of movable property and stress imposed on people as well, when performing demolition of a concrete structure - road section. Lack of literature is a big drawback, especially lack of norms for demolition works. Except for some unofficial lectures for internal use, most of the literature dates back to the seventies or early eighties. A special emphasis in this paper is given to the application of protective measures in the use of explosives. Introduction After the definition of demolition engineering works, the introductory part points to the distinction between the two types of demolition works: complete and partial. The concept of the organization of engineering works The basic definition of the organization of engineering works is given as well as an overview of the elements of preparatory work in the execution of engineering work on a particular construction. Demolition of a road section The concept of a road is explained as well as the methods of its demolition. The documents required for the organization of the demolition of a road section are presented as well as standards for the preparation of a road section for demolition. Safety and health at work with explosives Safety measures when working with explosives are explained in detail for different situations. Conclusion The importance of the organization of engineering works of demolition of a road section is explained, both under war and peacetime conditions.